Physicians’ Knowledge of Abdominal Compartment Syndrome and Intra-Abdominal Hypertension in Saudi Arabia: An Online Cross-Sectional Survey Study - Qutob R; Alkhannani AHA; Alassaf TY; Alhokail SO; Bagazi GA; Alsaleh AA; alqarni MK; Alammari Y; Al Harbi K; Elhazmi A; Bukhari AI; Alaryni A; et al. (International Journal of General Medicine, 2022)
Rayan Qutob,1,2 Alanoud Hassan A Alkhannani,1 Turki Yazeed Alassaf,1 Saad Othman Alhokail,1 Ghassan Abdullah Bagazi,1 Abdulmalak Abdullah Alsaleh,1 Mashael kamel alqarni,1 Yousef Alammari,1 Khalid Al Harbi,1 Alyaa Elhazmi,3 Abdullah Ibrahim Bukhari,1 Abdullah Alaryni,1 Abdullah Alghamdi,1 Osamah A Hakami1 1Faculty of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia; 2Adult Critical Care Department, Dr. Sulaiman Al-Habib Medical Group, Riyadh, Saudi Arabia; 3College of Medicine, AlFaisal University, Riyadh, Saudi ArabiaCorrespondence: Alanoud Hassan A Alkhannani, Faculty of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia, Tel +966 545436837, Email alanoudhk1998@gmail.comObjective: To determine physicians’ knowledge of abdominal compartment syndrome and intra-abdominal hypertension in Saudi Arabia.Methods: A cross-sectional online survey study was conducted on physicians in Saudi Arabia between March and August 2022. A previously developed questionnaire was adapted and used in this study. The survey instrument investigated the knowledge and management of intra-abdominal hypertension and abdominal compartment syndrome among physicians. Logistic regression was used to identify predictors of being knowledgeable about abdominal compartment syndrome and intra-abdominal hypertension.Results: A total of 266 physicians participated in this study. Around one-fifth (21.8%) the study participants were ICU physicians and 25.0% reported that they practice internal medicine. Intra-abdominal hypertension (IAH) and the impact of increased intra-abdominal pressure (IAP) on organ function were terms that the majority of research participants (70.3%) reported they were familiar with. A similar percentage (73.7%) reported that they are familiar with abdominal compartment syndrome (ACS). Around 43.0% of the study participants reported that they do not know how to measure IAP. The most frequently reported (13.5%) intervention in the treatment of IAH and ACS was the use of inotropes or vasopressors. The study participants showed a weak level of knowledge of ACS and IAH with a median score of 3.00 (IQR: 5.00– 2.00), which represents 27.3% of the maximum attainable score. Physicians working at hospitals with 20– 50 ICU beds were 41.0% (odds ratio: 0.59 (CI: 0.37– 0.96)) less likely to be knowledgeable about intra-abdominal hypertension and abdominal compartment syndrome (p≤ 0.05).Conclusion: Physicians demonstrated a low level of IAP and ACS knowledge. To increase the safety of medical practices and enhance clinical outcomes for patients, awareness should be raised about the proper diagnosis and management of IAP and ACS. Future research should focus on developing effective educational strategies to improve physicians’ understanding of IAP and ACS.Keywords: abdominal compartment syndrome, intra-abdominal hypertension, intra-abdominal pressure, knowledge, physicians, Saudi Arabia